Effect of Different Warm-up Procedures on the Performance of Resistance Training Exercises. Issue 1 (August 2014) - Ribeiro, Alex S.; Romanzini, Marcelo; Schoenfeld, Brad J.; Souza, Mariana F.; Avelar, Ademar; Cyrino, Edilson S.
Warm-up has been shown to mediate numerous acute physiological alterations that have been purported to confer beneficial effects on performance. This study investigated the acute effects of different warm-up procedures on resistance training performance. Employing a randomized, counterbalanced crossover design, 15 men performed 3 exercises (4 sets of bench press, squat, and arm curl at 80% of 1RM) to failure in 4 conditions (control, specific, aerobic, and combined). Outcome measures included the sum of repetitions and a fatigue index measuring the decline between sets. There was no significant difference for the sum of repetitions or for fatigue index among conditions for the 3 exercises. Performance in the resistance training exercises was not influenced by warm-up.